A Great Step Forward. Lithic Raw Material Procurement and Management among Palaeolithic Hunter-Gatherers in the Basque Crossroads. (2020) - , Maite García-Rojas; , Eder Dominguez-Ballesteros; ,; , Alejandro Prieto; ,; , Aitor Calvo; ,; , Aitor Sánchez; , Andoni Tarriño; Arrizabalaga, Alvaro
No abstract available